PENERBITAN SURAT BERLAYAR DI KANTOR PELABUHAN KELAS III JENEPONTO - ASRIANA, ASRIANA; NURMIATI, NURMIATI (Patria Artha Management Journal, 2024)
The aim of this research is to obtain an overview of the implementation of the policy for issuing sailing approval letters at the Jeneponto Class III Port Organizing Office. The population in this study were the parties involved in the issuance of the Sailing Approval Letter, consisting of all employees at the Jeneponto Class III Port Organizing Office, totaling 18 people and port service users, totaling 15 agents. The data analysis carried out was frequency distribution. The research results show that: a. Communication is good in terms of 1) Intensity of socialization of regulations for issuing sailing approval letters, 2) Consistency in policy orders for issuing sailing approval letters and 3) Clarity of communication between officers and port service users; b. Resources are good in terms of: 1) the ability and availability of human resources implementing the policy for issuing sailing approval letters, 2) the facilities needed to support the implementation of the policy for issuing sailing approval letters: c. Attitude (disposition) is good in terms of: 1) attitude of officers and port service users, 2) response of officers and 3) discipline of officers; d. The bureaucratic structure is good in terms of: 1) implementation of SOPs, 2) division of tasks, and 3) coordination of officers